Factors Related to Feelings of Loneliness and Attitudes Toward Ageing in Retired Older Adults - Fahime Rouhi; Shahla Asiri; Fataneh Bakhshi; Ehsan Kazemnezhad leili (Journal of Holistic Nursing and Midwifery)
Abstract Introduction: Feelings of loneliness and attitudes toward ageing in the elderly are associated with physical and psychological problems and increase the need for care services. Objectives: The purpose of this study was to investigate the factors related to feelings of loneliness and attitudes toward ageing in the elderly referred to centers covered by the country's pension fund Methods and materials: This cross-sectional study was performed on 235 elderly people covered by the Rasht State Pension Fund who were selected by proportionate stratified sampling. Data were collected using a demographic information checklist, Social and Emotional. Loneliness Scale for Adults (SELSA-S) and Aging Attitude Questionnaire (AAQ). Data analysis was performed using descriptive statistics, Spearman correlation coefficient, Mann-Whitney, Kruskal-Wallis tests, and multiple linear regression model. Results:The majority of samples (52.3%) were in the age range of 60 to 64 years. 53.6% of them were male and 93.2% were married. 51.1%  had high school  diploma. The mean scores of loneliness and attitudes toward ageing were 6.0 ±27.7and 7.3± 81.1 respectively. loneliness score was different based on  education (P = 0.004), monthly income (P = 0.017) and interacting with others (P = 0.035) and attitudes towards was statistically significant different based on  age (P = 0.002), post-retirement employment (P = 0.044), living status (P = 0.005), use of psychiatric drugs (P = 0.008) and interacting with others (P = 0.043) . Also, after adjusting the effects of individual-social variables using multiple linear regression, the attitude toward ageing was considered as a predictor of loneliness (B=-0.22, CI95% ;-0.33 to -0.11, P=0.001). Conclusion: Attitudes toward ageing are one of the predictors of loneliness in the elderly. Therefore, by modifying some demographic factors and designing interventions and educational programs, it is possible to change the attitude towards ageing and reduce the feeling of loneliness in the elderly.